Should UK primary care be an early adopter of genomic medicine? - Dickenson, D; Rafi, I; Spicer, J; Papanikitas, A (Royal College of General Practitioners, 2019)
Genomics is the study of all the DNA in the genome, together with technologies that allow it to be read, analysed and interpreted. Powerful new genomic technologies now allow greater accessibility to the human genome which is, in turn, allowing the integration of genomic data into all aspects of healthcare: increasingly genomic data are being used for the diagnosis and treatment of disease, and in due course are likely to be used for the prevention of disease. At the 2017 RCGP Annual Conference, the topic of whether UK primary healthcare should be an early adopter of genomic medicine was the subject of a debate led by the RCGP committee on medical ethics (CoME). By publishing this paper, we hope that readers who were unable to attend the conference debate will have an opportunity to consider the arguments and take the discussion further, whether in correspondence or on social media.